Tax Evasion In Iraqi Kurdistan - Shakhawan Khdir Rasul (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Taxes have been known for a long time, under the guardian state - and the phenomenon of tax evasion is one of the phenomena that most societies know as having existed by the existence of the tax itself, as it is a phenomenon that increases day after day with the increase in the volume of economic activity, something that complicates the legal data of the tax and thus disrupts development policy That the state controls, especially as it deprives it of large funds every year, but do not forget that the tax is the most important resource that contributed to financing the general budget, as well as an effective means to achieve economic balances and address them, but tax control cannot eliminate tax evasion and fraud alone, but other methods must be used. Such as using methods of prevention before evasion and fraud, And coordination between revenues to obtain the necessary information, and the importance of research lies by highlighting the tax policy trends used in Iraq and the Kurdistan Region and its role in measuring the amount of tax receipts for successive periods, and the research problem is the security, economic and political conditions that the Kurdistan Region has gone through with very difficult security conditions. The nineties of the last century until now, which led to the lack of clarity in the trends of tax policy and its volatility, This was reflected in the tax revenue increase or decrease, and despite many attempts to adjust tax rates in Iraq to keep pace with economic and social conditions. But sometimes it turns out that the legislator exaggerates the (exemptions) prescribed for a particular tax, so that the exemptions (exclusion) take advantage of larger areas than the tax (the original) to the extent that some people ask to question the possibility of canceling the tax imposition at all.